Structural Racism, Criminalization, and Pathways to Deportation for Dominican and Jamaican Men in the United States - Golash-Boza, Tanya Maria (Social justice, 2017)
The article discusses the effects of mass incarceration on the Black community in the U.S. Topics discussed include the practices associated with the criminalization of Black men, the impact of mass incarceration on the incorporation trajectories of Black male immigrants, and the role of criminalization and structural racism in these incorporation trajectories.